PENYELESAIAN PERJANJIAN KREDIT MACET DENGAN JAMINAN FIDUSIA ATAS KENDARAAN BERMOTOR DI PT. BANK PERKREDITAN RAKYAT BHUMIKARYA PALA YOGYAKARTA - , SAFITRI HARYA P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study about the resolution of non perfoming loan with fiduciary on motor vehicles in rural banks ( BPR ) Bhumikarya Pala Yogyakarta , and to determine the inhibitory constraints that occur in the loan resolution , and to know the efforts made for the settlement of non perfoming loans with fiduciary collateral on motor vehicle in BPR Bhumikarya Pala . The nature of this research is empirical juridical , which is a focus of research in the field of research to obtain primary data , by comparing its implementation on existing regulations . Then analyzed using qualitative methods to describe data obtained form the primary data , as well as secondary data obtained from the research literature , then be deduced . While the technique of making samplenya using non-random sampling technique , ie bank customers who have non perfoming loan with fiduciary collateral on motor vehicle . In this study show that the constraints that occur in the BPR Bhumikarya Pala is not list fiduciary as background factors and the cost of inter-bank competition , as well as fiduciary object whose condition is no longer complete or change shape , so its value down . Besides, in the process of selling objects uncooperative debtor fiduciary assurance submit objects that are still in their control . Therefore, the efforts made by the BPR Bhumikarya Pala is interm of debtor refusing to give the objects fiduciary collateral, Bank ask for hel to Police or courts, and the object of the sale is done either by the debtor fiduciary itself or by BPR Bhumikarya Pala . It is more efficient and is considered more beneficial to both parties than the settlement through an auction agency . Advice to the BPR Bhumikarya Pala is registering all fiduciary deed Fiduciary Registration Office to the Department of Law and Human Rights cq online , and do not carry Fiduciary Law partially . Keywords: Non Perfoming Loan, Fiduciary Collateral, Underhand of Sales